2004
DOI: 10.1007/s00216-004-2706-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of luminescent nanocrystals as labels for biological molecules

Abstract: Luminescent semiconductor nanocrystals, so called "quantum dots" (QD), have attracted increasing interest for bioanalytical labeling applications in recent years. This review describes the major optical and (bio)chemical features of this class of label, compared with organic dyes. Different conjugation methods are also discussed and the most important recent applications are presented. An overview over the current state-of-the-art is given, as also is an outlook on possibilities and limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 33 publications
1
58
0
Order By: Relevance
“…Recently, having intrinsic excellent optical properties, QDs have been tested as luminescent probes for biological processes, especially fluorescent biological labels and imaging, which have shown the potential biological applications of QDs (5)(6)(7)(8). Nowadays, however, highly efficient QDs are often synthesized in organic media, as such synthesis processes allow for advanced shape and composition control (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, having intrinsic excellent optical properties, QDs have been tested as luminescent probes for biological processes, especially fluorescent biological labels and imaging, which have shown the potential biological applications of QDs (5)(6)(7)(8). Nowadays, however, highly efficient QDs are often synthesized in organic media, as such synthesis processes allow for advanced shape and composition control (9).…”
Section: Introductionmentioning
confidence: 99%
“…The use of bioinorganic conjugates -QDs/protein systems -could overcome this problem and therefore represent an attractive tool as a novel method for use as bioactive fluorescent probes in sensing, imaging, immunoassays, and other diagnostics applications. [19,59,[78][79][80][81][82][83][84][85][86][87] In 1998, two research groups, Alivisatos et al [89] and Nie et al [56], reported the first use of quantum dots nanocrystals to label single molecules during living-cell assays and this topic is now being intensively investigated.…”
Section: Synthesis Of Colloidal Quantum Dotsmentioning
confidence: 99%
“…[120][121][122][123][124][125][126][127][128] Here we have selected to discuss a few representative publications that exploit unique quantum dot properties. Figure 60, core/shell quantum dots have narrow linewidths (~25nm FWHM) with a large range of tunability dependent upon the size and composition of the core.…”
Section: Overview Of Biological Applications Of Cdse/zns Nanocrystalsmentioning
confidence: 99%